Determination of Antioxidant Activity in Kombucha of Kecombrang Flower (Etlingera elatior) for the Development of Functional Beverages - Sintyadewi, Putu Rima; Fitriani, Pande P. Elza (Jurnal Pijar Mipa, 2024)
Researchers have widely reported that Kombucha is a probiotic drink with health benefits. Some researchers are innovating to find other kombucha media sources besides tea that contain high bioactive compounds. Kecombrang flowers contain high bioactive compounds and have physiological functions for health, but this plant has not been widely explored for other innovative beverage or food products. This study aimed to determine the optimal fermentation time of kecombrang flower kombucha (Etlingera elatior) to produce the highest antioxidant activity during fermentation. The experimental design used was a complete randomized design (CRD) with 7 variations of fermentation time (days 0, 3, 6, 9, 12, 15, and 18) with a sugar concentration of 10% b/v, and this treatment was repeated four times. In this research, pH, total acid, and total flavonoid tests were also carried out to see the characteristics of the kecombrang flower kombucha drink during fermentation. Data analysis was performed with an ANOVA at P < 0,05. The results showed that the length of fermentation time had a very significant effect (P < 0,01) on the antioxidant activity of Kombucha. These results indicate that the size of fermentation time affects the antioxidant activity of kecombrang flower kombucha. Optimal antioxidant activity was obtained after the kombucha drink was fermented for 6 days, as indicated by the low IC 50 value of 37,73 g/mL, with a pH of 3,7, total acid of 0,33%, and total flavonoids of 5,9 mg/L QE. Based on a research study, kecombrang flower kombucha has strong antioxidant activity (IC50 < 50 ppm), so kecombrang flower kombucha can be used as a choice for functional drinks.